By characterizing metabolic and immune microenvironment reveal potential prognostic markers in the development of colorectal cancer - Liao, Liangliang; Gao, Yongjian; Su, Jie; Feng, Ye (Frontiers in Bioengineering and Biotechnology, 2022)
Colon adenocarcinoma (COAD) is one of the deadliest cancers in the world and survival rates vary significantly between early and advanced stage patients. Therefore, identify the pathogenesis in the development of COAD and prognostic markers is urgently demanded. Herein, we collected RNA-seq profiles and somatic mutation data of COAD for statistical analysis. Stage-specific differentially expressed genes (DEGs) and tumor development-dependent DEGs were identified. By characterizing the metabolic and immune features of COAD between stages, we found that the energy supply and inflammatory response of advanced tumors were suppressed. Next, the ETS1, AR, GATA1, GATA2, SREBF1, FOXP3, STAT4, and NFKB1 were identified to drive the metabolic and immune-related pathways in the development of COAD. The three potential prognostic markers (HOXC8, IRF7, and CXCL13) were identified based on Cox regression analysis. Additionally, immune infiltration analysis revealed that the resting CD4+ T cell was significantly related to the overall survival (OS) of COAD patients. Identification of prognostic markers for COAD is essential for clinical diagnosis and treatment. Finally, the specific metabolic and immune characteristics of advanced patients and the identified driving factors will contribute to the development of precision medicine.